Serum INSL3 measured by LC-MS/MS in pubertal girls and in girls with precocious puberty during GnRH agonist treatment - Albrethsen, Jakob; Hagen, Casper P.; Juul, Anders (Frontiers in Endocrinology, 2024)
The peptide hormone Insulin-like Factor 3 (INSL3) is a biomarker of testicular Leydig cells in the male, but is also expressed by the theca cells of the ovaries. With the advent of sensitive assays INSL3 can be quantified in female circulation, and we suggest that circulating INSL3 is a novel biomarker for pubertal development in girls. The aim of the study is to quantify INSL3 by LC-MS/MS in sera from normal girls during pubertal transition, and during gonadal suppression by GnRH agonist therapy in girls with central precocious puberty (CPP). Thus, the sensitivity of an established LC-MS/MS-based method for serum INSL3 was improved by switching to a state-of-the-art triple quadruple mass spectrometer (Altis Plus, Thermo). This allowed for quantification of INSL3 in longitudinally collected serum samples during pubertal transition in healthy girls as well as in girls with CPP before, during and after treatment with GnRH agonist. The limit of detection of the LC-MS/MS method for serum INSL3 was 0.01 ug/L (1.5 pM) and the inter-assay CV was < 12%. Serum INSL3 increased during the pubertal transition in healthy girls and changes correlated with the concomitant rise in other measured hormones. In some girls, but not all, INSL3, FSH, inhibin B and estradiol serum concentrations increased prior to first clinical signs of puberty. Serum INSL3 concentrations were increased at baseline in girls with CPP compared to prepubertal controls and decreased during treatment with GnRH agonist followed by a steep rise and normalization after cessation of treatment. The improved LC-MS/MS-based method for serum INSL3 quantification allows for measurement of serum INSL3 in pubertal girls. Future studies are needed to clarify if INSL3 in combination with other biomarkers enhances the predictive value of differentiating between premature thelarche and CPP.